Review of Methods to Equate Target Sets in the Adapted Alternating Treatments Design. Issue 5 (September 2021) - Cariveau, Tom; Batchelder, Sydney; Ball, Sydney; La Cruz Montilla, Astrid
The adapted alternating treatments design is a commonly used experimental design in skill acquisition research. This design allows for the evaluation of two or more independent variables on responding to unique target sets. Equating target sets is necessary to ensure a valid comparison of the independent variables. To date, there is little guidance on best practice when equating target sets and it is unclear how researchers have done so previously. We reviewed the reported methods used to equate target sets in articles published using the adapted alternating treatments design in five behavior-analytic journals. Just over half of the studies published using the adapted alternating treatments design reported any method to equate target sets and the methods varied considerably. Alternative methods, such as random assignment, were prevalent. Considerations for best practice and avenues for future research are discussed.